2016
DOI: 10.1186/s12983-016-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of genetic uniqueness of populations may increase extinction likelihood of endangered species: the case of Australian mammals

Abstract: BackgroundAs increasingly fragmented and isolated populations of threatened species become subjected to climate change, invasive species and other stressors, there is an urgent need to consider adaptive potential when making conservation decisions rather than focussing on past processes. In many cases, populations identified as unique and currently managed separately suffer increased risk of extinction through demographic and genetic processes. Other populations currently not at risk are likely to be on a traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 59 publications
5
131
1
Order By: Relevance
“…Although it is possible that the partitioning of the Scotia Sanctuary bilbies into several largely self‐contained paddocks may have created cryptic genetic structure that was not captured by our opportunistic sampling regime, these results suggest that increased admixture would not only benefit the genetic health of the bilby population at this location but also play a crucial role in meeting the national recovery plan's target of maintaining 90% of current genetic variation among bilby populations for 100 years (Pavey ). The translocation of individuals between divergent populations (also known as genetic rescue) is currently underutilized as a conservation tool because of ongoing concerns about outbreeding depression and the dilution or loss of survival traits in local environments (Frankham , Weeks et al ). But the risks of outbreeding depression are minimal when the translocated animals are sourced from populations that occupy comparable environments, share the same karyotype, have previously experienced gene flow, or have long generation times (Frankham et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is possible that the partitioning of the Scotia Sanctuary bilbies into several largely self‐contained paddocks may have created cryptic genetic structure that was not captured by our opportunistic sampling regime, these results suggest that increased admixture would not only benefit the genetic health of the bilby population at this location but also play a crucial role in meeting the national recovery plan's target of maintaining 90% of current genetic variation among bilby populations for 100 years (Pavey ). The translocation of individuals between divergent populations (also known as genetic rescue) is currently underutilized as a conservation tool because of ongoing concerns about outbreeding depression and the dilution or loss of survival traits in local environments (Frankham , Weeks et al ). But the risks of outbreeding depression are minimal when the translocated animals are sourced from populations that occupy comparable environments, share the same karyotype, have previously experienced gene flow, or have long generation times (Frankham et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies using both mtDNA and microsatellite markers found no strong phylogeographical structure across the bilbies range, providing strong evidence for recent gene flow (Moritz et al ). Although there is some evidence for substantial sequence divergence among wild extant bilby populations (Moritz et al ), it has been argued that such uniqueness is more often a result of random genetic drift (and not selection) when identified using neutral genetic markers (Weeks et al ). Consequently, managing divergent populations (or captive individuals sourced from them) as entirely separate units may actively increase the species’ risk of extinction by further decreasing adaptive potential (Weeks et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This uniqueness most likely stems from genetic drift whose largest impact manifests in the most fragmented and isolated population. Therefore, focusing only on a few local populations as potential translocation units might further increase this fragmentation and might be ineffective in maintaining or increasing their adaptive potential in a time of progressing global warming and human pressure (Moritz 1994;Weeks et al 2016).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Although increasing neutral genetic diversity does not guarantee that the adaptive potential of species will be protected or increased, according to Weeks et al (2016), translocation experiments should be considered at the species level, rather than at a population, subspecies, or the ESUs levels (but see La Haye et al 2012). If so, translocation experiments between JW and Pannonian populations should be at least preliminary assessed in captivity given that: (1) genetic similarities between the currently geographically separated populations exist, both in mitochondrial and nuclear markers, e.g.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…the entire genetic richness of the species (Weeks et al 2016). Local adaptations can lead to a certain level of genetic differentiation, while still maintaining a cohesive general structure in a metapopulation framework.…”
Section: Introductionmentioning
confidence: 99%